2009
DOI: 10.1175/2009wcas1005.1
|View full text |Cite
|
Sign up to set email alerts
|

False Alarms, Tornado Warnings, and Tornado Casualties

Abstract: This paper extends prior research on the societal value of tornado warnings to the impact of false alarms. Intuition and theory suggest that false alarms will reduce the response to warnings, yet little evidence of a “false alarm effect” has been unearthed. This paper exploits differences in the false-alarm ratio across the United States to test for a false-alarm effect in a regression model of tornado casualties from 1986 to 2004. A statistically significant and large false-alarm effect is found: tornadoes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
85
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 15 publications
(22 reference statements)
4
85
1
4
Order By: Relevance
“…Brotzge and Erickson (2010) found that 73.6% of tornadoes in the 2000-04 period were associated with a NWS warning. Simmons and Sutter (2005) established that after the installation of the Weather Surveillance Radar-1988 Doppler (WSR-88D), the percentage of tornadoes warned increased to 60% from 35% prior to installation. A regression analysis of tornado casualties illustrated that expected fatalities were 45% lower for tornadoes occurring after installation of the new radar network.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Brotzge and Erickson (2010) found that 73.6% of tornadoes in the 2000-04 period were associated with a NWS warning. Simmons and Sutter (2005) established that after the installation of the Weather Surveillance Radar-1988 Doppler (WSR-88D), the percentage of tornadoes warned increased to 60% from 35% prior to installation. A regression analysis of tornado casualties illustrated that expected fatalities were 45% lower for tornadoes occurring after installation of the new radar network.…”
Section: Introductionmentioning
confidence: 99%
“…A regression analysis of tornado casualties illustrated that expected fatalities were 45% lower for tornadoes occurring after installation of the new radar network. Further investigation by Simmons and Sutter (2008b) determined that tornado warnings do reduce fatalities, and increased lead times for tornado warnings up to approximately 15 min reduced casualties, while longer lead times resulted in increased fatalities compared to no warning. The greatest reduction in fatalities occurs at lead times of 10-15 min, possibly because of the public concluding that the warning is a false alarm if a tornado does not occur soon after the warning is issued (Simmons and Sutter 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations